Nestedness of waterbird assemblages in the subsidence wetlands recently created by underground coal mining. Issue 2 (23rd April 2018) - Li, Chunlin; Zhao, Binbin; Wang, Yanping
Abstract: Nestedness has been a research focus in fields of island biogeography and community ecology in recent decades. Although nestedness of faunal assemblages has been investigated in natural wetlands, it remains largely unknown whether and why waterbird communities in artificial wetlands follow nested patterns. We examined the existence of nestedness and underlying drivers in waterbird communities in subsidence wetlands that are recently created by large-scale underground coal mining in the North China Plain. Twelve point-count surveys for waterbirds were undertaken approximately every 2 weeks in 55 subsidence wetlands from September 2016 to April 2017. We used the metric WNODF to estimate nestedness of the assemblages. Partial Spearman rank correlations were performed to examine the association between the nestedness and habitat variables (wetland area, landscape connectivity, wetland age, and habitat diversity) as well as life-history traits (body size, clutch size, dispersal ratio, geographical range size, and migrant status) related to species extinction risk and colonization rate. Waterbird assemblages in the subsidence wetlands were significantly nested. After controlling for other independent variables, the magnitude of nestedness was significantly and negatively correlated with wetland area and species trait linked to extinction risk (i.e., geographical range size). Our results indicate that selective extinction may be the main driver of the nestedness of waterbird assemblages in our study system. However, the nestedness was not due to passive sampling, selective colonization, or habitat diversity. From a conservation viewpoint, both large wetlands and waterbirds with a small geographic range should be protected to maximize the preserved species richness.